Rhodium and Iridium Mediated C-H and O-H Bond Activation of Two Schiff Base Ligands: Synthesis, Characterization and Catalytic Properties of the Organometallic Complexes - Sengupta, Poulami; Das, Rituparna; Dhibar, Papu; Paul, Piyali; Bhattacharya, Samaresh (Frontiers in Chemistry, 2021)
Abstract: Reaction of [Rh(PPh3)3Cl] with two Schiff base ligands, viz. N-(2′-hydroxyphenyl)furan-2-aldimine (H2L1) and N-(2′-hydroxyphenyl)thiophene-2-aldimine (H2L2), in refluxing toluene affords organorhodium complexes of type, [Rh(PPh3)2(L)Cl] (L = L1 and L2). Similar reaction with [Ir(PPh3)3Cl] yields organoiridium complexes of type [Ir(PPh3)2(L)(H)] (L = L1 and L2). Crystal structures of [Rh(PPh3)2(L1)Cl] and [Ir(PPh3)2(L2)(H)] have been determined, where the imine ligands are found to bind to the metal centers as CNO-donors. Structures of [Rh(PPh3)2(L2)Cl] and [Ir(PPh3)2(L1)(H)] have been optimized by DFT method. Formation of the organometallic complexes is believed to proceed via C-H and O-H bond activation of the imine ligands. All four complexes show intense absorptions in the visible and ultraviolet regions. Cyclic voltammetry on the complexes shows an oxidation on the positive side of SCE and a reduction on the negative side. The organoiridium complexes are found to efficiently catalyze Suzuki-type C-C cross coupling reactions.